2018
DOI: 10.1016/j.jfca.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients, phytochemicals and botanical origin of commercial bee pollen from different geographical areas

Abstract: Abbreviations 18AA: amino acid; BP: bee pollen; DBP: dried bee pollen; MUFA: monounsaturated fatty acids; 19 PA: polyamine; SFA: saturated fatty acids; TL: total lipid; UFA: unsaturated fatty acids 20 2 ABSTRACT 21 22This work evaluated the nutritional, phytochemical composition and botanical origin of 23 commercial bee pollen from three different countries. Fructose (17-23%) was the most 24 abundant sugar in all samples, followed by glucose (14-16 %) and sucrose (5-6%). The 25 protein content in Colombian (24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
47
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 23 publications
10
47
0
5
Order By: Relevance
“…The fatty acid profile obtained in this work was similar to that reported in previous studies . However, when studying Romanian pollen, Mărgăoan et al observed greater diversity: 14 fatty acids were identified.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The fatty acid profile obtained in this work was similar to that reported in previous studies . However, when studying Romanian pollen, Mărgăoan et al observed greater diversity: 14 fatty acids were identified.…”
Section: Discussionsupporting
confidence: 89%
“…[8,10,[29][30][31][32] However, when studying Romanian pollen, Maȓgaȏan et al [6] observed greater diversity: 14 fatty acids were identified. Apart from the importance of the botanical origin, it has been reported that the lipid profile of bee pollen depends on the geographic origin, [29,30] edaphoclimatic conditions as well as on the apicultural practices. As stated by Saa-Otero et al, [32] these variations are due, partly, to the fact that these compounds may result from the secondary metabolism of plants, which themselves are variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollen is a fine yellow-red powder-like material produced by flowering plants and is gathered by bees [1]; it results from the agglutination of flower pollen, the nectar of honey and the salivary substances from the bees [2]. The chemical composition of bee pollen depends on several factors, such as plant source, geographical origin, seasonal conditions and bee activities [3,4]. The main constituents of pollen are: proteins [2,4], carbohydrates [4,5], lipids [4,5], amino acids [4,5], polyphenols [4,6,7] and carotenoids [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…19%), glucose (approx. 15%) and sucrose (7%), while the main fatty acids are linoleic (18:2n-6), α-linolenic (18:3n-3) and palmitic (16:0) acids [2,4,5]. The color of pollen is given by the presence of the flavonoids and carotenoids (lutein, β-cryptoxanthin and β-carotene) [8].…”
Section: Introductionmentioning
confidence: 99%